Penyelenggaraan Piala Dunia U-17 di Indonesia Tahun 2023 Dilihat Melalui Dimensi Diplomasi Publik - Rahman, Rayyan Ramadana; Alexandra, Frisca; Anggraini, Yayuk (Department of International Relations, Universitas Mulawarman, 2026)
This study aims to analyze Indonesia's public diplomacy through the organization of the 2023 FIFA U-17 World Cup as an effort to restore its national image in the global arena, following the Kanjuruhan tragedy and the cancellation of the 2023 FIFA U-20 World Cup. This research employs a qualitative approach using library research and internet-based sources, framed by two dimensions of Mark Leonard’s three-dimensional public diplomacy model, namely news management and strategic communication. The findings reveal that the hosting of the U-17 World Cup in Indonesia was not merely a sporting event, but also an effective instrument of public diplomacy. By applying Leonard’s dimensions of public diplomacy, Indonesia successfully rebuilt a positive international image, promoted its soft power through cultural and sports appeal, and strengthened international relations. This inclusive and positive approach demonstrates that sports, particularly football, can serve as a powerful tool for building bridges between nations and shaping a more favorable global perception of Indonesia.